Does quality of alternatives matter for internet banking?. (17th March 2008) - Shi, Weihua; Lee, Cheng-Few
This study aims to examine how the quality of service alternatives influences Internet Banking (IB)customers' behaviours. Although the newly developed IB is a fast-growing channel, the traditional brick-and mortar face-to-face banking services are still pervasive. Therefore, it is important to understand how the quality of alternatives (traditional banking services) influences customers' behaviours. In the present study, we proposed that quality of alternatives dampens the perception of service quality, value, satisfaction and ultimately customer's intention of using IB. The model was tested using survey data from 156 individuals who were using IB. The results indicated that the quality of alternatives has both direct and indirect influences on IB customers' behaviours.